THE USE OF AUTHENTIC MATERIALS IN DEVELOPING COMMUNICATIVE COMPETENCE. - Bozorboeva Lobar Alisher qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract This article examines how authentic materials—texts, audio, video, and visual media not originally created for language learners—enhance learners’ communicative competence in EFL/ESL contexts. Drawing upon empirical studies and theoretical discourse, we argue that authentic materials boost motivation, cultural awareness, listening and reading proficiency, and the pragmatic use of language. While benefits clearly outweigh drawbacks, careful task design and balanced integration are necessary to mitigate challenges such as learner frustration or cognitive overload. We recommend a calibrated inclusion of authentic materials (approximately 50 %) in curricula to maximize communicative development.